Can assessment of disease burden and quality of life based on mobility level in patients with end-stage cancer provide an insight into unmet needs? An exploratory cross-sectional study - AKYÜZ, GÜLSEREN DERYA (My University, 2022)
Purpose The purpose of this study was to: 1) investigate the differences in the needs of end-stage cancer who can move independently, using mobility aids (MA), or are bedridden; and 2) determine the effects of these different mobility levels on the patients\" current quality of life (QoL), fatigue, and mental conditions. Methods The study employed an exploratory prospective cross-sectional study design, which was carried out in two hospitals. The study included 99 end-stage cancer. The mobility levels of the patients were evaluated in three groups: Group 1: bedridden; Group 2: mobile with MA; and Group 3: ambulatory (under supervision or fully independent). A core cancer-specific questionnaire-integrating system for assessing health-related QOL (EORTC-QLQ-C15-PAL), the Piper Fatigue Scale (PFS), and the Hospital Anxiety-Depression scale were utilized. The median age was 60years (31-83). Cancer types were as follows: gastrointestinal (45.5%), lung (38.4%), breast (4%), genitourinary system (4%), and others (8%). Forty-two percent of the patients were completely bedridden, 42.2% used MA, and 15.2% were independently ambulatory. The EORTC QLQ-C15-PAL physical (=.000) and emotional function values (=.029) differed among mobilization statuses. There was a significant difference among mobilization groups, in terms of behavioral values, in the PFS (=.006). The depression rate in the independent ambulatory group was lower than in the bedridden and MA groups (=0.011; =0.004). p p p p1 p2 Conclusion Health-related QoL, fatigue level, and emotional state vary in end-stage cancer who undergo evaluations according to their mobility levels. These patients should be assessed comprehensively, and treatment plans should be organized carefully, with a multidisciplinary approach.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Medicine; Health Sciences; Internal Medicine Sciences; Physical Medicine and Rehabilitation; REHABİLİTASYON; Klinik Tıp; Klinik Tıp (MED); REHABILITATION; CLINICAL MEDICINE; Clinical Medicine (MED); Chiropractics; Rehabilitation; Physical Therapy, Sports Therapy and Rehabilitation; Cancer; end-stage; palliative care; rehabilitation; PHYSICAL-ACTIVITY; EORTC QLQ-C15-PAL; CARE NEEDS; PALLIATIVE CARE; TURKISH VERSION; FATIGUE; BREAST; ASSOCIATIONS; RELIABILITY; SURVIVAL